Slovenian Civil Registration and Unique Identification Number System for Universal Health Coverage : A Case Study - Zorko Kodelja, Martina; Mills, Samuel (World Bank, Washington, DC, 2019)
A health protection system based on social health insurance has had a long tradition in Slovenia. Several forms of health insurance schemes were implemented from 1896 until 1992, when health care reform legislation was passed, establishing compulsory health insurance (CHI). CHI is provided by a single provider the Health Insurance Institute of Slovenia (HIIS), which is a public legal entity. Everyone with permanent residency in Slovenia is covered under the unique CHI scheme, either as a mandatory member or as a family dependent. The system is funded through CHI contributions of employees and employers (for the active population), and other required contributions (by the self-employed, farmers, pensioners, etc.). The entire population is insured. Since the establishment of HIIS in 1992, the implementation of information and communications technologies (ICTs) to support key CHI processes has been a matter of strategic importance. HIIS has developed an information center to support CHI’s key business processes. Infrastructure, applications, data, and security systems in the central public administration are being increasingly integrated to provide citizens with comprehensive services, and to facilitate their access to them. E-government is the area in which the expectations, needs, and habits of citizens are linked to the business processes of the public sector, as well as to e-business technological solutions. Because e-government projects in Slovenia have been introducing e-business into public administration over the past decade, the exchange of data between institutions has been improved and technologically updated.